The Use of The Round-Robin Technique on Students’ Vocabulary Mastery for The Second Graders of SMK Al Maksum Langkat - Malau, Khairunnisa Br.; Rahmadhani, Maitri; Suprayetno, Edi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The objective of this research was to determine whether the Round Robin technique significantly affects students’ vocabulary mastery for the second graders of SMK AL Maksum Langkat. A quasi-experimental research design was used in this study. There were 51 students taken as sample by using purposive sampling technique from 116 populations of second graders of SMK AL Maksum Langkat. There were 28 students from class XI OTKP as a control class, and 23 students from class XI as an experimental class. There were six meetings conducted by the researcher which consisted of one meeting for pre-test, four meetings for treatments, and one meeting for the post-test. The Round Robin technique was applied to the experimental class and the conventional technique was applied in the control class. From the analysis of the data by using Independent Sample T-test in SPSS 25.00 it was found that the data were in normal distribution and had the same variance or homogenous. The result of the hypothesis test showed that the students’ mean score of pre-test was lower than the post-test (79,30 > 53,11) and the Sig. (p value) < ? = 0.05 (0,000 < 0,05), it can be said that H0 was rejected and Ha was accepted. it can be concluded that there was a significant effect of using the Round Robin technique on students’ vocabulary mastery in the second graders of SMK AL Maksum Langkat.